Pendampingan Industri Kreatif pada Usaha Kecil Menengah (UKM) di Sentra Pengrajin Dompet “Macakal” Guna Meningkatkan Daya Saing Pasar di Kabupaten Lebak Provinsi Banten - Mislan Mislan; Lucky Setiawan; Ari Handoko; Dedy Khaerudin; Irma Nurmala Dewi (Jurnal Nusantara Berbakti, 2025)
The contribution of artisans to the enhancement of the economy in Indonesia, particularly within the home industry sector of small and medium enterprises (SMEs) located in the "Macakal" creative industry center, is of paramount significance for the economic advancement of the community in Lebak Banten Regency. The "Macakal" creative industry produces various products, including woven wallets, synthetic leather wallets, laptop bags, small wallets, and agenda covers. The traditional woven fabric of Banten, which is not widely known by the public, is used as the main material for making wallets and other products at this SME "Macakal." In the development of this home industry, the entrepreneurs encounter difficulties in the form of business capital and also a lack of consumer interest post-COVID-19. The stakeholders in the home industry, known as "Macakal," acknowledge the support provided by the local government in terms of business capital. Additionally, they emphasize the importance of organizing exhibitions and programs aimed at promoting the home industry within Lebak Regency. The solution offered in this assistance is the introduction of products from the "Macakal" home industry center through social media and also through the mass media, as well as local government providing business capital assistance so that entrepreneurs can develop their businesses again. The outcome of this PKM initiative is that the home industry entrepreneurs known as "Macakal" are now able to promote their products via social media and comprehensive internet marketing strategies. This advancement has facilitated an expansion of their market reach and contributed to the enhancement of the economic conditions of small and medium-sized enterprises (SMEs)